Pengaruh Faktor Kepuasan Kerja terhadap Produktivitas Kerja Karyawan pada Koperasi Serba Usaha SuksmaningIdep Drana Ika (SIDI) - PEBRIANA, I MADE WAHYU; AMBARAWATI, I GUSTI AGUNG AYU; DJELANTIK, A.A.A. WULANDIRA SAWITRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
The Influence of Job Satisfaction Factors on Employee Productivity at Suksmaning Idep Drana Ika (SIDI) Business Cooperative The development of cooperatives is currently supported by the development of small and medium enterprises (SMEs). One of the multi-business cooperatives in Denpasar is the Suksmaning Idep Drana Ika (SIDI) multi-businessCooperative which was established on November 16, 1951. The cooperative must increase its productivity so that the cooperative's goals can be optimally achieved, one of them by paying attention to employee job satisfaction.The purpose of this study was to determine employee job satisfaction and the influence of job satisfaction factors on employee work productivity at the SIDI Multi-business Cooperative. The sampling technique was done by census, as many as 46 employees as respondents. Employee job satisfaction was measured by four factors, namely psychological, financial, social, and physical factors. Measurements are measured in ordinal by using a Likert Scale. The data analysis method used is SEM-PLS, using the help of the Smart PLS V.3.0 application. The results showed that employee job satisfaction was in the satisfied category and job satisfaction factors significantly influenced employee work productivity. This means that job satisfaction factors along with their indicators play an important role in reflecting work productivity. Physical factors have a dominant influence on employee work productivity at the SIDI Multi-business Cooperative.